APEC ODR Framework: Prospects and Challenges of Its Implementation in Indonesia - Putra, Ida Bagus Wyasa (Kertha Semaya : Journal Ilmu Hukum, 2023)
The APEC ODR Framework is an ambitious project to support Indonesian MSMEs’ strategic position and function in the Asia-Pacific economy. The Indonesian government aims to protect them from any impediment, including the impact of business disputes. Numerous professional forums have been held to assess the framework’s performance, but they have primarily focused on the internal system component while ignoring some fundamental issues of the framework’s external system. This article examines such issues as: first, why the recent assessment model would fail to support the future need for the framework’s effective work; and second, what kind of law and policy scheme would adequately support the future need for the framework’s effective work. Based on McDougal’s contextual approach, the analysis has produced two conclusions: first, the recent assessment model has focused primarily on assessing the internal system. Some determining components of the external system have not been assessed, such as the state legal culture and the MSMEs’ corporate culture; second, the formulation of the law and policy scheme for supporting the effective work of the framework shall cover the needs for shifting the state legal culture, particularly on recognition and execution of the foreign arbitral award, including the revision of Article 65 up to Article 69 of the Indonesian Act on Arbitration and ADR of 1999, and the needs for developing a new corporate culture on the ODR settlement of dispute for shifting the MSMEs legal culture form the court culture into ODR culture.